(untitled) (African Journal of Biomedical Research, 2023)
Cutaneous pox is an insidious proliferative disease characterized by the lesions such as thick scabs, small nodules, wart-like masses on the skin of avian species. This disease can be confused with other diseases and conditions such avian papilloma, infraorbital sinusitis, infectious coryza and trauma. To detect the causative agent of the lesions, samples of suspected pox lesions were collected from sixteen turkey poults. Polymerase chain reaction (PCR) and sequencing analysis were employed to detect the causative agents responsible for the lesions. PCR was used to amplify FPV 167, FPV 140 and thymidine kinase genes of avipoxvirus. Eight (50%) out of the 18 samples tested positive using PCR. Sequence analysis based on multiple sequence alignment and phylogenetic tree reconstruction revealed the causative agent to be fowlpox virus. Also, amino acid substitutions P25S, S26P, G49E, V142I and V252M in FPV 167 gene, and T78K, I79I and A92G in thymidine kinase gene were revealed to clearly distinguish fowlpox virus from other avipoxviruses analyzed. This study demonstrated the importance of employment of molecular tools PCR and sequence analyses for precise identification and characterization of causative agents of infectious diseases.